Hubungan Pemanfaatan KB Suntik dengan Fisiologi Siklus Menstruasi pada Akseptor KB - Yuli Bahriah; Yuni Kurniati (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
In Indonesia, KB injection is one of the popular and widely used methods. This study aims to determine the relationship between the use of KB injection and the physiology of the menstrual cycle in KB Acceptors. This study uses a descriptive analytical method with a data collection method based on a time approach with a cross-sectional method. The results of the bivariate analysis obtained a p value = 0.000. This means that a p value of 0.000 <α = 0.05 means that there is a significant relationship between the use of KB injection and the physiology of the menstrual cycle in KB acceptors at PMB Yuli Bahriah, Kertapati Village in 2025. The contingency coefficient (C) value was obtained, namely 0.642, which means that it has a value with a strong association conclusion. The use of the DMPA type of KB injection and the Cyclofem type of KB injection has different effects on changes in the physiology of the menstrual cycle. DMPA KB injection users are more likely to experience abnormal menstrual cycles (Oligomenorrhea, Polymenorrhea, Amenorrhoea) meaning that the physiology of their menstrual cycle is disturbed. Meanwhile, users who use the Cyclofem KB injection experience more normal menstrual cycle physiology.